The neonicotinoid insecticide Clothianidin adversely affects immune signaling in a human cell line. Issue 1 (December 2017) - Di Prisco, Gennaro; Iannaccone, Marco; Ianniello, Flora; Ferrara, Rosalba; Caprio, Emilio; Pennacchio, Francesco; Capparelli, Rosanna
Abstract Clothianidin is a widely used neonicotinoid insecticide, which is a potent agonist of the nicotinic acetylcholine receptor in insects. This neurotoxic compound has a negative impact on insect immunity, as it down-regulates the activation of the transcription factor NF-κB. Given the evolutionary conserved role of NF-κB in the modulation of the immune response in the animal kingdom, here we want to assess any effect of Clothianidin on vertebrate defense barriers. In presence of this neonicotinoid insecticide, a pro-inflammatory challenge with LPS on the human monocytic cell line THP-1 results both in a reduced production of the cytokine TNF-α and in a down-regulation of a reporter gene under control of NF-κB promoter. This finding is corroborated by a significant impact of Clothianidin on the transcription levels of different immune genes, characterized by a core disruption of TRAF4 and TRAF6 that negatively influences NF-κB signaling. Moreover, exposure to Clothianidin concurrently induces a remarkable up-regulation of NGFR, which supports the occurrence of functional ties between the immune and nervous systems. These results suggest a potential risk of immunotoxicity that neonicotinoids may have on vertebrates, which needs to be carefully assessed at the organism level.